TSirk . The Circus - Aleksandrov, Grigori (Soviet Union, 1936)
A highly popular Soviet musical comedy. Marion Dixon is an American circus artiste, on tour with her German manager, von Kneischitz. When she falls in love with a Russian engineer, her manager tries to blackmail her by revealing that she has given birth to a child out of wedlock, and that the baby is black. His plot backfires when she finds happiness and acceptance among the Soviet people.